2018
DOI: 10.1002/bab.1658
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models for the effect of temperature on flavonoid production in liquid submerged fermentation by Phellinus baumii

Abstract: Kinetic models and temperature control strategy were established to reflect the effect of temperature (22 °C-30 °C) on flavonoid production of Phellinus baumii (P. baumii) in 6-L fermentor. A modified Logistic equation, Hinshelwood model, and Luedeking Piret equation were used to describe mycelial growth and product formation. The influence of temperature on the estimated kinetic parameters was further studied by regression analysis. Based on kinetic parameters analysis, the new temperature control strategy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…There were lots of kinetic models including parameters related to light intensity, light quality, and temperature for microalgae growth . The growth curves of microalgae under 10% CO 2 and different simulated flue gases were correlated by the equation below . dCdt=μmax1CCmaxCCfalse(tfalse)=C0·Cmax·eμmax·tCmaxC0+C0·eμmax·t…”
Section: Methodsmentioning
confidence: 99%
“…There were lots of kinetic models including parameters related to light intensity, light quality, and temperature for microalgae growth . The growth curves of microalgae under 10% CO 2 and different simulated flue gases were correlated by the equation below . dCdt=μmax1CCmaxCCfalse(tfalse)=C0·Cmax·eμmax·tCmaxC0+C0·eμmax·t…”
Section: Methodsmentioning
confidence: 99%
“…Based on kinetic parameters analysis, a temperature control strategy (30 C to 28 C for 0-43 h, 28 C to 24 C for 43-90 h, 24 C for 90-161 h) was proposed to shorten the lag phase of mycelial growth, keep high avonoid productivity and relieve inhibition of avonoids. By this temperature control strategy, the maximum avonoid yield reached 42.1 mg g À1 dry cell weight, which was 70.45% higher than that at a constant temperature of 26 C. 38 Using model-based temperature prole (0-20 h 30 C, 20-72 h 40 C), Xie et al increased the glycerol yield by 12-14%, while the residual glucose was less than 1% (w/v). 31 By programmed controlling of the incubation temperature (0-24 h 37 C, 24-144 h 25 C) and using the optimized medium, Shen et al increased the alcohol concentration to 6.97 g L À1 in carbon monoxide-rich off-gas fermentation using Clostridium carboxidivorans.…”
Section: Variable Parametersmentioning
confidence: 98%
“…In addition, it was found that the contents of active compounds and their biological activities in artificial cultivated fruiting bodies of Sanghuangporus were higher and stronger than those in wild ones [ 13 , 14 ]. Therefore, several strategies were applied into the mycelium cultures or fruiting body cultivation to improve the efficiency and quality of Sanghuangporus production, including mutation breeding [ 15 ], the optimization of medium composition [ 16 ], the improvement of cultural condition [ 17 ], and the addition of exogenous fungal elicitor [ 18 ]. It was worth mentioning that the growth and development of both wild and cultivated macrofungal fruiting bodies were in association with various endophytic microorganisms, in which the community structures and roles of bacteria inhabiting in fruiting bodies have been widely explored and reported.…”
Section: Introductionmentioning
confidence: 99%